A Leadership Training Group for at Risk Fifth & Seventh Graders: Results from A Brief Strength-Based Group Program. Issue 3 (3rd July 2018) - Dennison, Susan T.; Daniel, Stephanie S.; Gruber, Kenneth J.; Cavanaugh, Alyson M.; Mayfield, Andrew
ABSTRACT: An increasing number of youth are exhibiting social, emotional, and behavioral problems that hinder their ability to function at grade level. Subsequently, school mental health services have not been able to address the need for services particularly among students who are minority and poor. A mixed methodology study was conducted to determine the treatment outcomes from a brief strength-based leadership training group for primarily students who are African American and poor. Pre–post scores on three scales and focus group data revealed significant positive changes in regard to internal areas of functioning and social skills, anger management skills, and school attitude. Gender and age significantly impacted outcomes.